2005
DOI: 10.1021/jp0537207
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study toward Understanding Ultrafast Internal Conversion of Excited 9H-Adenine

Abstract: The CASPT2/CASSCF method with the 6-311G basis set and an active space up to (14, 11) was used to explore the ultrafast internal conversion mechanism for excited 9H-adenine. Three minima, two transition states, and seven conical intersections were obtained to build up the two deactivation pathways for the internal conversion mechanism. Special efforts were made to explore the excited-state potential energy surfaces near the Franck-Condon region and determine the various barriers in the processes of deactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
158
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(170 citation statements)
references
References 22 publications
11
158
1
Order By: Relevance
“…4a. It should be noted that a similar scenario has been proposed and discussed for Cyt 32 and Ade 33 . However, we believe that this scenario should be valid for all DNA nucleobases since the only dark state common to all nucleobases is the nπ * state.…”
mentioning
confidence: 59%
“…4a. It should be noted that a similar scenario has been proposed and discussed for Cyt 32 and Ade 33 . However, we believe that this scenario should be valid for all DNA nucleobases since the only dark state common to all nucleobases is the nπ * state.…”
mentioning
confidence: 59%
“…17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42 It has been demonstrated that the fast deactivation of NABs after UV light absorption is due to a barrierless decay of the bright spectroscopic ππ* singlet excited state towards the ground state. Femtosecond pump-probe experiments with the canonical NABs reported multiexponential decay channels in the femtosecond and picosecond timescales, a strong evidence for the stability of the natural NABs.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the *͞n * proximity effect explains neither the methylation nor solvation effects (for details, see ref. 1), and many theoretical studies have sought to explain the discrepancies (4,9,10,13,15,20,(23)(24)(25)(26). Interestingly, these time-resolved ion yield studies did not reveal differences between adenine and 9-methyl adenine (19,22), thus apparently disfavoring the * channel.…”
mentioning
confidence: 97%
“…Studies of the UV absorption spectrum showed that the 252-nm band is predominantly a transition to an optically bright * state (6,7). However, very close in energy lie at least one other much darker * state, the optically dark n * state, and a * state that is discussed in more detail below (1,4,(8)(9)(10). A widely accepted mechanism for adenine electronic relaxation involves two sequential steps: *3 n * followed by n *3S 0 (ground state) internal conversion (1).…”
mentioning
confidence: 98%